2017
DOI: 10.1107/s2059798317011822
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the interaction of the conserved mammalian proteins GAPR-1 and Beclin 1, a key autophagy protein

Abstract: Mammalian Golgi-associated plant pathogenesis-related protein 1 (GAPR-1) is a negative autophagy regulator that binds Beclin 1, a key component of the autophagosome nucleation complex. Beclin 1 residues 267-284 are required for binding GAPR-1. Here, sequence analyses, structural modeling, mutagenesis combined with pull-down assays, X-ray crystal structure determination and small-angle X-ray scattering were used to investigate the Beclin 1-GAPR-1 interaction. Five conserved residues line an equatorial GAPR-1 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…Previous studies indicated that autophagy activation has a dual effect on the occurrence of tumors [37]. In most cases, it was shown that activated autophagy of cancer cells can induce autophagic cell death, which may represent a promising approach for cancer treatment [19][20][21][22][23][24][25][26][27][28][29][30][31]. In the present study, we showed that Glut-1 knockdown evoked autophagy activity in HEp-2 cells leading to subsequent cell apoptosis, suggesting that Glut-1 may be a novel inducer of cell autophagy and useful for the treatment of laryngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies indicated that autophagy activation has a dual effect on the occurrence of tumors [37]. In most cases, it was shown that activated autophagy of cancer cells can induce autophagic cell death, which may represent a promising approach for cancer treatment [19][20][21][22][23][24][25][26][27][28][29][30][31]. In the present study, we showed that Glut-1 knockdown evoked autophagy activity in HEp-2 cells leading to subsequent cell apoptosis, suggesting that Glut-1 may be a novel inducer of cell autophagy and useful for the treatment of laryngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activated ATG1 can form a protein complex through a series of ubiquitination-like ligation reactions with other autophagy-related factors, such as ATG3 and ATG5, in a manner dependent on the activity of phosphorylated Beclin-1 [43]. Beclin-1 is a key protein in the process of autophagy in mammalian cells and is a direct mediator of autophagy [20,28,29,43]. Beclin-1 protein complex mediates autophagosome formation at the start of autophagy [20,28,29,43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations